The Americans - Roderick, David (Pitt poetry series., 2014)
David Roderick's second book, The Americans, pledges its allegiance to dirt. And to laptops. And to swimming pools, the Kennedys, a flower in a lapel, plastic stars hanging from the ceiling of a child's room, churning locusts, a jar of blood, a gleam of sun on the wing of a plane. His poems swarm with life. They also ask an unanswerable question: What does it mean to be an American? Restless against the borders we build-between countries, between each other-Roderick roams from place to place in order to dig into the messy, political, idealistic and ultimately inexplicable idea of American-ness.